2003
DOI: 10.1074/jbc.m301279200
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin and Neph1 Co-localize at the Podocyte Foot Process Intercellular Junction and Form cis Hetero-oligomers

Abstract: Glomerular visceral epithelial cells (podocytes) appear to play a central role in maintaining the selective filtration barrier of the renal glomerulus. While the immunoglobulin superfamily member Nephrin was proposed to act as a cell adhesion molecule at the podocyte intercellular junction necessary for maintaining glomerular perm selectivity, the Nephrin ligand has not been identified. The existence of a new subfamily of Nephrin-like molecules including Neph1 was recently described. Genetic deletion of Nephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(164 citation statements)
references
References 34 publications
8
150
0
6
Order By: Relevance
“…9,10,52 It was suggested that the interaction between nephrin and Neph1 partially stabilizes the interaction between Neph1 and ZO-1. 10 The question of how these two cell adhesion systems contribute to the regulation of slit diaphragms remains to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,52 It was suggested that the interaction between nephrin and Neph1 partially stabilizes the interaction between Neph1 and ZO-1. 10 The question of how these two cell adhesion systems contribute to the regulation of slit diaphragms remains to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Neph1 binds to the PDZ domain of ZO-1 via its C-terminal PDZ-binding motif. 13,21 Next, we tested using GST pulldown assay whether nephrin also binds to not only MAGI-1 but also ZO-1.…”
Section: Nephrin Does Not Bind To Zo-1mentioning
confidence: 99%
“…11 Neph1 shows high expression in the kidney and is colocalized with nephrin at the podocyte foot process. 12,13 The deletion of Neph1 in the mice results in proteinuria. 11 a-Actinin-4, an actin-binding and crosslinking protein, is highly expressed in podocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the precise molecular structure of the SD is still unresolved. Recently identified podocyte proteins, such as nephrin, Neph1, Neph2, FAT1, FAT2, and dendrin probably form the backbone of SD [6][7][8]. These proteins associate with each other extracellularly and interact with the adapter proteins, such as podocin, CD2AP, ZO-1, CASK, and MAGI-1, localized in the cytosolic part of the podocyte.…”
Section: Glomerular Filtration Barriermentioning
confidence: 99%